2011
DOI: 10.1021/nl202943b
|View full text |Cite
|
Sign up to set email alerts
|

Rational Synthesis of Silver Vanadium Oxides/Polyaniline Triaxial Nanowires with Enhanced Electrochemical Property

Abstract: We designed and successfully synthesized the silver vanadium oxides/polyaniline (SVO/PANI) triaxial nanowires by combining in situ chemical oxidative polymerization and interfacial redox reaction based on β-AgVO(3) nanowires. The β-AgVO(3) core and two distinct layers can be clearly observed in single triaxial nanowire. Fourier transformed infrared spectroscopic and energy dispersive X-ray spectroscopic investigations indicate that the outermost layer is PANI and the middle layer is Ag(x)VO((2.5+0.5x)) (x < 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 37 publications
1
90
1
Order By: Relevance
“…When the current rate was lowered back to 30 mA g -1 , the discharge capacity rebounded to about 150 mAh g -1 , showing good electrochemical reversibly. These results are better than previously published results [6][7][8].…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…When the current rate was lowered back to 30 mA g -1 , the discharge capacity rebounded to about 150 mAh g -1 , showing good electrochemical reversibly. These results are better than previously published results [6][7][8].…”
Section: Resultscontrasting
confidence: 76%
“…L.Q. Mai et al [6] , with only 30% capacity retention after 20 cycles. S. Liang et al [7] reported simple synthesis using a soft chemical method without a template.…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR spectrum of phytic acid doped PAni indicates that it is the emeraldine salt form of PAni with two characteristic peaks located at 1,570 and 1; 480 cm −1 corresponding to the stretching vibration of the quinoid ring and benzenoid ring (16,17), respectively. The state of these products was emeraldine rather than solely leucoemeraldine or permigraniline (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…43 Figure 1b It is obvious that sample 450 has a larger curve area and a higher redox peak current than those of samples 400 and 500, suggesting that sample 450 has the highest capacity and the fastest kinetics for Li ion insertion/extraction. 41,44 Sample 450 is used as an example to explain the electrochemical process. All of these peaks originate from the phase transitions between Li 1 þ x V 3 O 8 components with different x values (0oxo3).…”
Section: Characterization Of LIV 3 O 8 Nanowiresmentioning
confidence: 99%